Psychological manifestations in post myocardial infraction patients - Singh, Sanjay; Kanwar, Gopal; Paikra, Shashi; Pandey, Sachin (International Journal of Medical Research and Review, 2018)
Background: In the past few years a very important observation that came to light is the increase in prevalence of some psychiatric disorder in chronically ill patients. Symptoms of depression and anxiety are common following myocardial infarction (MI). Both the symptoms have been linked with increased risk of recurrent coronary artery disease (CAD), Severe psychological stress, major life events, and depression causes myocardial infarction (MI) in 15% of case of Coronary Artery Disease (CAD) and are associated with higher rates of morbidity and mortality. Objective: (1) To establish the diagnosis of myocardial infarction in patients. (2) To study and correlate various psychological manifestations in these patients. Methodology: The patients for the present study were taken up from those admitted in ICCU and OPD of department of Medicine G.M.C, Ambikapur, during the study period. 50 patients were studied having CAD (Myocardial infarction). The patients were history taken in detailed & examined (Physical and Psychiatric), investigated with reference to ECG proven myocardial infarction or cardiac enzymes proven MI. Results: We have found 46% of prevalence rate of depression in our study. Majority of patients (20%) have mild depression (score 10-13) on (HAD-Scale), 12% have major depression, 42% had Anxiety. Majority of patients 26% have mild anxiety. Only 6% have severe anxiety (score > 30) in our study. Conclusion: Personality feature of CAD patients are associated with emotional as sympathetic arousal which result in increases in catecholamine as consequent increase in mobilization of free fatty acid from adipose tissue, aggregation of platelets which may precipitate MI. So, a thorough research, prevention and rehabilitation of psychologically oriented care can increase the patients sense of security and is fundamental basis of successful medical care.